Risk and management of ocular bleeding associated with oral anticoagulants - Koh, Len V; Gosnell, Chad E; Well, Anna R (Canadian Journal of Optometry, 2019)
Deep vein thrombosis, pulmonary embolism, ischemic stroke and myocardial infarction are the major thromboembolic diseases which affect millions of North Americans. Most of these patients are managed long term with oral anticoagulants that can increase the risk of bleeding including ocular hemorrhages. As primary eye care providers, optometrists do encounter patients presenting with ocular bleeding secondary to oral anticoagulants. This article provides an overview and update of oral anticoagulants, and discusses ways to manage ocular bleeding associated with oral anticoagulants via two clinical cases. Interruption of anticoagulation temporarily increases thromboembolic risk, and continuing anticoagulation increases the risk of bleeding, both scenarios adversely affect patient’s overall health. Eye care providers must work closely with primary care provider and/or anticoagulation team to come up with the best decision on an individual patient basis with respect to each ocular bleeding occurrence.